The Preferred Language of Media Content among the Serbian Diaspora in Vienna - Miketić Subotić, Sanja D. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
This paper aims to determine the preferred language (Serbian, German, or another) of various types of content—music, TV programs, films, books, newspapers and magazines, radio, and news—among members of the Serbian diaspora in Vienna. The research included a heterogeneous group of randomly selected adults who identified themselves as Serbs or of Serbian origin and had resided in Vienna for at least one year (N = 400). Participants reported their typical language choices using a closed-ended questionnaire, and the data were analyzed using SPSS software. The variables used in this paper were: age, gender, language of questionnaire completion, mother tongue, country of birth, migrant generation, length of residence in Austria, educational level, language spoken by parents, partner, and friends, ethnic and cultural self-identification, return migration intentions, and religious involvement (church attendance). This study aims to investigate how domain-specific language preferences among members of the Serbian community in Vienna are shaped by a complex interplay of biographical proximity to the heritage language, social embeddedness in Serbian-speaking networks, and ideological alignment with ethnocultural identity. Rather than treating language choice as a static reflection of individual attributes, the study seeks to uncover the sociolinguistic conditions under which language practices emerge, persist, or shift in transnational contexts. We concluded that media language choice within this community is shaped less by traditional sociodemographic variables and more by affective, symbolic, and contextual factors tied to identity, intimacy, and migration stage. The findings revealed a clear preference for Serbian in emotionally salient media such as music and books, while a balanced use of both Serbian and German was observed in other media domains.